Perempuan Hamil G1P0A0 dengan Preeklamsia Berat : Laporan Kasus - Muhammad Rayza Rahmatullah; Ratna Dewi Puspitasari (CV. Jasa Sukses Abadi, 2026)
Severe preeclampsia is a pregnancy complication that contributes to increased maternal and perinatal morbidity and mortality. Accurate diagnosis and management are essential to prevent more serious complications. This case report aims to describe the clinical manifestations, risk factors, management, and outcomes of a patient with severe preeclampsia. A 29-year-old woman, G1P0A0, at 39 weeks of gestation, presented with uterine contractions and blood-tinged mucous discharge. The patient had a history of elevated blood pressure since 32 weeks of gestation. Physical examination revealed a blood pressure of 152/112 mmHg, while urinalysis demonstrated positive proteinuria. Laboratory findings showed hemoglobin 13.9 g/dL, leukocytes 12,900/µL, and platelets 228,000/µL. Ultrasonography revealed a single live fetus in cephalic presentation with an estimated fetal weight of 3,302 grams. The patient was diagnosed as G1P0A0 at 39 weeks of gestation, in active phase of the first stage of labor, with severe preeclampsia. She received magnesium sulfate as seizure prophylaxis and nifedipine as an antihypertensive agent. During observation, fetal distress was identified, necessitating pregnancy termination via cesarean section. The infant was born weighing 3,200 grams with Apgar scores of 8/9. The mother's postoperative condition was stable, with blood pressure decreasing to 116/83 mmHg. This case demonstrates that severe preeclampsia may present without characteristic symptoms. Early detection, close monitoring, and appropriate management play a crucial role in achieving favorable maternal and neonatal outcomes.